Imaging strategies for follow-up during adjuvant nivolumab in esophageal cancer: A multicenter retrospective cohort study - Tamara J. Huizer; Anniek Strijdhorst; Laurens V. Beerepoot; Mark I. van Berge Henegouwen; Leni van Doorn; Sarah Derks; Bas P. L. Wijnhoven; Bianca Mostert; Hanneke W. M. van Laarhoven (PLoS ONE, 2026)
Introduction Adjuvant nivolumab improves disease-free survival in patients with esophageal or gastroesophageal junction cancer following neoadjuvant chemoradiotherapy and resection, but recurrence risk remains high. Optimal follow-up strategies for early detection of recurrence during nivolumab treatment are lacking. Methods In this multi-center, retrospective cohort study, patients from three hospitals in the Netherlands who underwent surgical resection between September 2021 and October 2023 and received adjuvant nivolumab were included. Data on tumor type, treatment, and imaging intervals (every 3 months vs every 4 months) were collected. Primary outcome was disease recurrence, secondary outcomes included disease-free survival (DFS), and diagnostic yield of CT scans. Results Of 353 patients that underwent resection, 151 received at least one dose of adjuvant nivolumab (82% male; median age 66 years; 86% adenocarcinoma). A total of 27 patients (18%) developed on-treatment recurrent disease, which was detected by routinely performed CT scans in 67% and included distant metastasis in 89%. DFS was 89% at 4 months, 84% at 8 months, and 75% at 12 months, showing a gradual decline over time. The diagnostic yield of CT scans increased from 0% at baseline to 9% at 4 months. Conclusion Routine baseline CT imaging did not detect recurrences, while routine imaging during adjuvant nivolumab identified the majority of recurrences. The gradual decline in disease-free survival suggests that recurrences are distributed over time, supporting a routine imaging interval, such as every 3 or 4 months as used in our study. These real-world data may help inform clinicians, and future studies can further evaluate optimal imaging intervals.